Communication skills: what do employers' expect? (workplace communication skills for engineering graduates) - Sivanganam, Lalithambigai (2002)
A brilliant engineer who cannot communicate is a matter to be taken seriously. What will happen to Malaysia if we keep churning out thousands of brilliant engineers but when it comes to employability skills, they are retarded? Malaysian engineering graduates especially are handicapped when it comes to communicating in English. English language is the international language used for education, business and technology. Therefore, it is crucial that an engineer masters the art of communicating in English as well as engineering knowledge. Thus, this research is conducted to find out what communication skills that the employers in the industry deem that their employees should have? However, this research only focuses on engineering graduates and the manufacturing industry. The researcher intends to learn the importance that is given to communication skills by the industry and whether it helps an engineering graduate to be promoted and be successful in their jobs. After obtaining the results from the employers, the researcher will suggest recommendation to improve the course content of KUiTTHO's Communication Skills course to be parallel with the demands of the industry.